MORPHOMETRIC CHANGES IN THE TESTIS AGAINST THE BACKGROUND OF CHEMOTHERAPY-INDUCED RENAL FAILURE AND THEIR BIOCORRECTION - Y.U., Joynarov; N.R, Ishburiev; U.M, Shermatov; Z.Sh, Abulfayzov; M.O, Djuraev (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study investigates the effects of chemotherapy-induced renal impairment on testicular morphology and evaluates the efficacy of a biocorrective intervention aimed at mitigating associated reproductive damage. Method: Conducted at the Department of Trauma Outcomes and Orthopaedics, Surkhandarya Multidisciplinary Medical Centre, the study utilized an animal model to simulate cytotoxic therapy-induced renal failure. Histological and morphometric analyses of testicular tissue were performed, focusing on parameters such as seminiferous tubule diameter, spermatogenic stratification, and interstitial cell function. A biocorrective agent with antioxidant properties was administered to assess restorative outcomes. Results: Chemotherapy-induced renal dysfunction resulted in significant structural alterations in the testes, including reduced spermatogenic activity and cellular degeneration. Treatment with the biocorrective compound led to partial restoration of testicular architecture and improved cellular integrity. Novelty: The study provides new insights into the systemic consequences of chemotherapy, particularly its underrecognized impact on male reproductive health, and demonstrates the therapeutic potential of targeted biocorrection in preserving gonadal function. These findings support a more integrative, organ-preserving approach in oncology care that prioritizes long-term quality of life alongside cancer eradication.